2016
DOI: 10.3390/cryst6100123
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Study of Optoelectronic Trapping on Iron-Doped Lithium Niobate Substrate

Abstract: Optoelectronic tweezers (OET) are a promising technique for the realization of reconfigurable systems suitable to trap and manipulate microparticles. In particular, dielectrophoretic (DEP) forces produced by OET represent a valid alternative to micro-fabricated metal electrodes, as strong and spatially reconfigurable electrical fields can be induced in a photoconductive layer by means of light-driven phenomena. In this paper we report, and compare with the experimental data, the results obtained by analyzing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…These characteristics together with its efficiency and low cost are making PVT a competitive tool for organic and inorganic particle manipulation. This technique has been successfully applied in different fields including (i) microfluidics for microdroplet dynamic deformation, patterning, and splitting [12][13][14] and particle desorption mass spectrometry microchannel fabrication [15], (ii) plasmonics, as a tool for obtaining plasmonic platforms for fluorescence enhancement of organic and biomolecules [16], (iii) biophotonics and biomedicine as a method of killing cancer cells [17] and for bacteria, pollen, and spore arranging [18,19], and (iv) photonics, for the fabrication of flexible diffractive optical elements [20].…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics together with its efficiency and low cost are making PVT a competitive tool for organic and inorganic particle manipulation. This technique has been successfully applied in different fields including (i) microfluidics for microdroplet dynamic deformation, patterning, and splitting [12][13][14] and particle desorption mass spectrometry microchannel fabrication [15], (ii) plasmonics, as a tool for obtaining plasmonic platforms for fluorescence enhancement of organic and biomolecules [16], (iii) biophotonics and biomedicine as a method of killing cancer cells [17] and for bacteria, pollen, and spore arranging [18,19], and (iv) photonics, for the fabrication of flexible diffractive optical elements [20].…”
Section: Introductionmentioning
confidence: 99%
“…In that work, the crystal substrate had the polar axis parallel to the surface, x-or y-cut, (see Figure 2a,b). A recent work [27] includes a theoretical study for the same x-/y-cut geometry and using a very similar model than that of reference [26] but applied to a cylindrical light beam. Additionally, since 2013 another configuration with the polar axis normal to the surface, i.e., z-cut, (see Figure 2c) has been often employed in relation to 2D patterning (see Section 3) and a simple model to describe it has been already reported [28,29].…”
Section: Physical Basis Of the Pv Methodsmentioning
confidence: 99%
“…Gazzeto et al [27] reported in 2016 that they were not able to observe DEP force on dielectric particles dispersed in water or any aqueous solution. No trapping or repulsive DEP force was observed on micro-particles in aqueous medium.…”
Section: Droplet Manipulationmentioning
confidence: 99%
“…The continuing popularity of LiNbO 3 in this area originates from its highly desirable properties, such as large electro-optic, acousto-optic, piezoelectric and nonlinear optical coefficients, and its quite easy production in a single-domain state 2,3 . Moreover, this material has recently been proposed as optically active substrate for the realization of microfluidic devices 4,5 , thus paving the way for its use in the optofluidic field. On the other hand, liquid crystals (LC) are known for their sensitiveness to external stimuli, among which optical and electric fields are widely used in photonics and display applications 6,7 .…”
Section: Introductionmentioning
confidence: 99%